Parametric study of stresses in cooling-tower shells - Ajayi, Olugbenga Olumide (Department of Civil Engineering, 2023)
Many attempts have been made in studying the structural behaviour of cooling tower shells, focusing more on the effect of wind on the structure and shape imperfections. However, little has been investigated on the most basic loading condition, i.e. self-weight load. This thesis focuses on a cooling tower with uniform thickness where several geometric parameters like the hyperbolic axis ratio (bla), top opening angle , offset parameters (A), and scale of the structure are varied one at a time, to investigate the effect these parameters have on the meridional and hoop stresses. A general-pwpose finite element programme, ABAQUS, was used to create models of the cooling tower structure. The model results were verified using closed-form analytical membrane solutions as reported by Zingoni. The model considers constraining the base against rotation in all directions while the top is made to be free. The predicted numeric meridional and hoop stresses compare favourably well with the closed-form analytical results, except at the critically stressed zone near the base that exhibits some bending disturbances. Parametric investigation shows that an increase in the hyperbolic axis ratio, the top opening angle, and offset paramete also increases meridional and hoop stresses. It is concluded that lower blao, and zero offset parameters be adopted for preliminary design purposes. Finally, recommendations are made on the need for further investigations.